BRAND ENGAGEMENT AS A MEDIATOR : CONNECTING BRAND FAMILIARITY, SELF-IDENTIFICATION AND POSITIVE WORD OF MOUTH - Salfiana, Eganadzmi; Masnita, Yolanda (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The Covid-19 pandemic has heightened public awareness of the importance of health products such as hand sanitizers, which became essential during the pandemic. This study aims to analyze the influence of brand fit on brand familiarity, customer brand engagement, self-identification, and word-of-mouth (WOM) for hand sanitizer products registered with the Ministry of Health (Kemenkes) and the National Agency of Drug and Food Control (BPOM). The research employs a hypothesis-testing method with a cross-sectional design, involving 170 respondents selected through purposive sampling based on the criteria of active hand sanitizer users. Data were collected using a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM), which includes Confirmatory Factor Analysis (CFA) and hypothesis testing. The results indicate that brand fit significantly influences brand familiarity and customer brand engagement. Furthermore, customer brand engagement was found to affect self-identification, which ultimately has a significant impact on WOM. This study reinforces the theories of Consumer-Based Brand Equity, Engagement Theory, and Social Identity in explaining the relationships between brand fit, consumer engagement, and self-identification in shaping consumer decisions to recommend brands.The practical implications of this research highlight the importance of brand fit and customer brand engagement in fostering brand loyalty, consumer trust, and positive WOM. Marketing strategies that focus on packaging visualization, brand image, and relevant product functions can strengthen a brand's position in an increasingly competitive market. This study provides a significant contribution to the marketing literature by adding brand fit as a key factor in creating relevant and meaningful brand experiences for consumers